Second Five Year Plan of the Information and Publicity Department, Government of Vindhya Pradesh November 1955 - Planning Commission (Planning Commission, 1955)
The Second Five Year Plan of the Information and Publicity Department, Vindhya Pradesh (1955) outlines a comprehensive strategy to strengthen government–public communication in a largely rural and low-literacy context. Recognizing the department’s formative stage, the plan emphasizes decentralized and culturally rooted methods of information dissemination, including community listening schemes, mobile publicity units, documentary films, and local information centres. Special attention is given to folk songs, drama, exhibitions, and vernacular publicity literature as effective tools for rural engagement. Supported by targeted funding and institutional arrangements, the plan aims to foster informed public participation, bridge the gap between the administration and citizens, and align communication efforts with broader developmental objectives of the Second Five-Year Plan.
Government of Vindhya Pradesh November 1955
Government of Vindhya Pradesh November 1955
Keywords: Information and Publicity Planning; Vindhya Pradesh Second Plan; Community Listening Scheme; Community Radio Sets; Mobile Publicity Vans; Information Centres Network; Documentary Film Production; Publicity Literature Programs; Press Advertisement Strategy; Folk Songs and Drama Outreach; Rural Communication Methods; Cultural Engagement Initiatives